(untitled) (Al-Academy, 2019)
This research provides a study of the virtual museums features and characteristics and contributes to the recognition of the diversity of visual presentation methods, as the virtual museums give the act of participation and visual communication with programs at an open time, so that it would contribute to reflection, thinking and recording notes, developing the actual and innovative skills through seeing the environments. The study has been divided into two sections the first one is virtual museum techniques. The techniques were studied to reach the public and are used remotely by the services of personal computers or smart phones being virtual libraries that store images and information that was formed and built in a digital way and how the aesthetics of the virtual museum had a profound effect on reception. The second section was the aesthetics of the imaginary space in the virtual museum to study the analysis of the samples, the diversity of presentation methods in virtual museum space. The research ended up with the results and conclusions. The importance of virtual museums which invest that space in the presentation is that they present information in a simple and interesting way in receiving the experiences and the viewer has the freedom to choose the distance in which he sees the work and the ease of touching the different dimensions of objects through the sense of sight. The virtual museums are areas located within the Internet whose purpose is advertising and defining a museum which could have no presence in reality. The use of virtual museums technologies, and accelerated technical progress and developments in the field of communication and technology and the growing interest in knowledge and discovery increased. The research ended up with some recommendations and proposals.